Metabolic Labeling of Prenylated Proteins Using Alkyne‐Modified Isoprenoid Analogues. Issue 3 (30th July 2018) - Suazo, Kiall F.; Hurben, Alexander K.; Liu, Kevin; Xu, Feng; Thao, Pa; Sudheer, Ch.; Li, Ling; Distefano, Mark D.
Abstract: Protein prenylation involves the attachment of a farnesyl or geranylgeranyl group onto a cysteine residue located near the C‐terminus of a protein, recognized via a specific prenylation motif, and results in the formation of a thioether bond. To identify putative prenylated proteins and investigate changes in their levels of expression, metabolic labeling and subsequent bioorthogonal labeling has become one of the methods of choice. In that strategy, synthetic analogues of biosynthetic precursors for post‐translational modification bearing bioorthogonal functionality are added to the growth medium from which they enter cells and become incorporated into proteins. Subsequently, the cells are lysed and proteins bearing the analogues are then covalently modified using selective chemical reagents that react via bioorthogonal processes, allowing a variety of probes for visualization or enrichment to be attached for subsequent analysis. Here, we describe protocols for synthesizing several different isoprenoid analogues and describe how they are metabolically incorporated into mammalian cells, and the incorporation into prenylated proteins visualized via in‐gel fluorescence analysis. © 2018 by John Wiley & Sons, Inc.